Role of Localized States on Carrier Transport in Bulk Heterojunction Materials Comprised of Organic Small Molecule Donors. (19th December 2013) - Zhong, Chengmei; Huang, Fei; Cao, Yong; Moses, Daniel; Heeger, Alan J.
<x xml:space="preserve">Abstract</x> The photocarrier transport properties in two leading molecular bulk‐heterojunction systems, p‐DTS(PTTh2)2:PC71BM and p‐DTS(FBTTh2)2:PC71BM, are studied using transient photoconductivity measurements. We find that in these systems shallow trap states are distributed at relatively narrow energy range, giving rise to time‐independent carrier mobility in the nanosecond time regime that evidently contributes to the high performance of molecular‐based OPV devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>